Evaluation of the effects of regulatory T cells on survival outcomes in patients with acute leukemia who developed febrile neutropenia - Sebnem Calik; Oktay Bilgir; İsmail Demir; Selma Tosun; Yeliz Özdemir (Journal of International Medical Research)
Objectives Acute leukemia often leads to severe complications such as febrile neutropenia. Mortality rates remain high, underscoring the need for novel prognostic markers. Regulatory T cells (Tregs) have not been extensively studied in this context. Methods This prospective observational, single-center study included 114 patients diagnosed with acute leukemia. Tregs percentages were measured using flow cytometry. Statistical analyses involved logistic regression to identify factors significantly associated with survival. Results Of the 114 patients, 78 recovered, while 36 died. The median Treg percentages were 5.9% in patients under 65 years and 5.38% in those 65 and older. A lower percentage of Tregs was associated with higher mortality in the older group (p = 0.04). Multivariate analysis highlighted the presence of comorbidities, documented infections, and day seven C-reactive protein levels as significant predictors of survival. Conclusion This study supports the importance of monitoring chronic diseases and infection foci alongside traditional markers like C-reactive protein. Future research should explore the mechanistic roles of Tregs in immunosuppression and survival in this vulnerable population.